Reflecting upon reflections - Zeitler, H.; Camp, D. (Teaching Mathematics and Computer Science, 2009)
This paper considers many applications of reflections in geometry. It begins with a few motivational problems for the classroom and goes on to consider the formal application to cases involving reflections across one line, two lines and three lines. It wraps up with a summary of results for reflections in higher orders.All this stuff was treated in German and American schools too – so the paper is a typical example of German-American didactics."Thinking is one of the greatest pleasure of mankind." – Galileo Galilei